2011
DOI: 10.4049/jimmunol.1002400
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B4 Mediates Neutrophil Migration Induced by Heme

Abstract: High concentrations of free heme found during hemolytic events or cell damage leads to inflammation, characterized by neutrophil recruitment and production of reactive oxygen species, through mechanisms not yet elucidated. In this study, we provide evidence that heme-induced neutrophilic inflammation depends on endogenous activity of the macrophage-derived lipid mediator leukotriene B4 (LTB4). In vivo, heme-induced neutrophil recruitment into the peritoneal cavity of mice was attenuated by pretreatment with 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 43 publications
1
43
0
1
Order By: Relevance
“…LTB4 levels in supernatants of monocytes stimulated with LPS increased with time and peaked at 3 h, similar to prior studies with human alveolar macrophages (33). Heme alone induced a slight increase in LTB4 (34). However, the combination of LPS and heme (1 μmol/L) led to significantly higher concentrations of LTB4 in the culture medium ( Figure 7A).…”
Section: Hx Blocks Synergistic Production Of Ltb4 Induced By Hemin Ansupporting
confidence: 70%
See 1 more Smart Citation
“…LTB4 levels in supernatants of monocytes stimulated with LPS increased with time and peaked at 3 h, similar to prior studies with human alveolar macrophages (33). Heme alone induced a slight increase in LTB4 (34). However, the combination of LPS and heme (1 μmol/L) led to significantly higher concentrations of LTB4 in the culture medium ( Figure 7A).…”
Section: Hx Blocks Synergistic Production Of Ltb4 Induced By Hemin Ansupporting
confidence: 70%
“…An alternative possibility would be that hemopexin bound cell-free heme that induced or primed macrophages to produce chemotaxins such as leukotriene B4 (LTB4). LTB4 has been described as the major chemotaxin induced by heme (34). In our studies, none of the Hx preparations, regardless of protease activity, directly suppressed neutrophil migration.…”
Section: Discussionmentioning
confidence: 54%
“…The authors thank Luis Ferreira Moita (Instituto Gulbenkian de Ciência) for critical review of the manuscript and Zélia Gouveia for producing the heme structures in Figure 1 Mø [59,61,62,[67][68][69] and endothelial cells [20]. In some cases this is mediated via a mechanism involving heme sensing by PRR [20,27,28] as well as G coupled proteins…”
Section: Acknowledgementsmentioning
confidence: 99%
“…LTB 4 , which is known as a potent chemoattractant, has been shown to induce activation and migration of leukocytes (32,33). It has been shown that both alox5 knock-out and Alox5 inhibitor treatment lead to a decrease of in vivo leukocyte inflammatory migration of mice (34).…”
mentioning
confidence: 99%